Efektivitas Penerapan Pengendalian Internal Kontrol Terhadap Pendapatan Asli Daerah Kabupaten Nagan Raya - Yusri Yusri; Cut Delsie Hasrina (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2018)
Internal control is important thing  in running a system both in government and private sector. This study  was using  primary data from the  interviews with employees of the Regional Financial and Asset Management Agency (BPKAD) office in Nagan Raya District. The analysis method used was descriptive analysis method by describing the findings obtained from the study. The results of this study indicated that the application of an internal control system for the aquisition of Regional Revenue of Nagan Raya District was sufficient because sufficient segregation of duties has been carried out, the forms used in tax payments have contained reliable information, responsibilities given and documents related to local tax revenues clear and coordinated.